Penguatan Kesehatan Finansial dan Kesehatan Mental pada Kelompok Istri Petani di Jombang - Elva Farihah; Bani Bacan Hacantya Yudanagara; Shochrul Rohmatul Ajija; Fahmi Idris; Amelia Rosikhotul Ulum (JAST : Jurnal Aplikasi Sains dan Teknologi, 2025)
The problem faced by the farmers' wives group partners in Tebel Village, Bareng District, Jombang Regency, is a lack of knowledge in managing family finances, which can lead to increased financial pressure and psychological stress. This program aims to provide education on financial literacy, wise household financial management, and mental health literacy to improve partners' mental health. Participants are given socialization related to financial health education and mental health education. Apart from that, participants are also invited to practice directly preparing a household budget in a simple and easy-to-understand manner. Pre-tests and post-tests are also administered to evaluate the level of achievement of the service program. Additionally, a feedback questionnaire was provided to participants as a means of evaluating the implementation of activities and assessing the sustainability of the community service program. Based on the analysis of the pre-test and post-test results, participants have increased knowledge in managing financial health and mental health. By integrating knowledge about financial planning and mental health, this activity had a significant positive impact on the farmers' wives in Tebel Village, Bareng District, Jombang Regency.ABSTRAKPermasalahan yang dihadapi oleh mitra kelompok istri petani di Desa Tebel, Kecamatan Bareng, Kabupaten Jombang adalah minimnya pengetahuan dalam mengelola keuangan keluarga sehingga dapat meningkatkan tekanan finansial dan tekanan stess secara psikologis. Kegiatan ini bertujuan untuk memberikan edukasi mengenai literasi keuangan mengenai pengelolaan keuangan rumah tangga yang bijak dan literasi kesehatan mental untuk meningkatkan kesehatan jiwa mitra. Peserta diberikan sosialisai berkaitan dengan edukasi kesehatan finansial dan edukasi kesehatan mental. Selain itu, peserta juga diajak untuk praktek secara langsung menyusun anggaran rumah tangga dalam lingkup yang sederhana dan mudah dipahami. Pre-test dan post-test juga diberikan untuk mengevaluasi tingkat ketercapaian program pengabdian. Selain itu, kuisioner umpan balik juga diberikan kepada peserta sebagai bentuk evaluasi pelaksanaan kegiatan dan untuk keberlanjutan program pengabdian masyarakat. Berdasarkan analisis deri hasil pre-test dan post-test, peserta memiliki peningkatan pengetahuan dalam mengelola kesehatan keuangan dan kesehahatan mental.  Dengan mengintegrasikan pengetahuan tentang perencanaan keuangan dan kesehatan mental, kegiatan ini berhasil memberikan dampak positif yang signifikan bagi para istri petani di Desa Tebel, Kecamatan Bareng, Kabupaten Jombang.